Undercurrents reasons for outrage, optimism, and seizing opportunities to change the world. - Davis, Steve (Business leader and activist) (JOHN WILEY & Sons, 2020)
"Undercurrents teaches readers and activists how to invest time, talent, voice, and cash to improve the world by detailing six of the largest macrotrends shaping the world today. Those 6 macrotrends are: The world is becoming a diamond (the shift in the distribution of wealth) Communities are the customer Digital technology is a bridge; not a divide The last mile is no longer the hardest (the greatest need and hardest work lies not at the beginning of the journey OR in reaching the goal; it's the path you take to get there) Adaptation and access trump invention Complex partnerships yield the best results The book strives to create a shared understanding of the true shape of the world in the 21st century, supported by data, stories, experiences, and observations to promote well-being across many facets of society. Undercurrents frames Davis' ideas as a business leader and practitioner to help the interested become educated, the committed become activists, and the engaged become more effective"--